2012
DOI: 10.1016/j.pacfin.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The investment value of the value premium

Abstract: Value investment strategies are premised on research that value stocks outperform growth stocks. However, the research findings are dependent on the portfolio classification method that is used to sort stocks using the attributes of size and book-tomarket ratios. Different stock markets contain different distributions of stocks, and in many markets, illiquidity concerns combined with a lack of investment scale, effectively create barriers to practical portfolio formations that align with the research. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 27 publications
3
47
1
Order By: Relevance
“…In particular, the skew in the Australian market means that prior studies utilize portfolios that have a much larger proportion of total market capitalization assigned to the largest size quintile and a significantly smaller proportion in the smallest size quintile. While prior Australian studies generally do not find evidence of a value premium, when Brailsford et al (2011) employ a portfolio construction method which parallels the standard US approach, a value premium is clearly apparent.…”
Section: Prior Researchmentioning
confidence: 85%
See 2 more Smart Citations
“…In particular, the skew in the Australian market means that prior studies utilize portfolios that have a much larger proportion of total market capitalization assigned to the largest size quintile and a significantly smaller proportion in the smallest size quintile. While prior Australian studies generally do not find evidence of a value premium, when Brailsford et al (2011) employ a portfolio construction method which parallels the standard US approach, a value premium is clearly apparent.…”
Section: Prior Researchmentioning
confidence: 85%
“…In a recent study, Brailsford, Gaunt and O'Brien (2011) draw attention to the portfolio construction method employed in prior Australian studies. They show how it is critically different to that employed in the US market.…”
Section: Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Fama and French (1998), studies such as Brailsford et al (2012), Asness et al (2013), and Ebrahim et al (2014a) also find the value premium in developed markets (such as the Australia, Continental Europe, Japan, UK and USA) and various developing ones (such as Brazil, China, India, and Turkey). 2…”
Section: Notesmentioning
confidence: 99%
“…Baltussen et al (2012) analyzed the US yearly data from 1963 to 2007, and concluded that the value premium was smaller for investors such as ISSN 2157-6068 2014 www.macrothink.org/bms 70 pension funds and insurance companies, especially when they were downside risk averse. Brailsford et al (2012) examined the value premium in the Australian stock markets, and they suggested that the existence of the value premium depended on the portfolio formation methodology. They concluded that the state of the value premium in Australia was not always the same as that in the US stock markets.…”
Section: Literature Reviewmentioning
confidence: 99%